Human exposure to F-53B in China and the evaluation of its potential toxicity: An overview. (March 2022) - He, Yanxia; Lv, Di; Li, Chuanhai; Liu, Xiuqin; Liu, Wendong; Han, Wenchao
Highlights: F-53B has been ubiquitously detected in humans. F-53B can induce lipid metabolism, endocrine disorders and foetal growth in humans. The biological toxicity of F-53B and its potential mechanisms have been reviewed. Abstract: Chlorinated polyfluoroalkyl ether sulfonic acid (Cl-PFESAs, trade name F-53B), an alternative to perfluorooctane sulfonate (PFOS), has been widely used as a mist suppressant in the Chinese electroplating industry since the 1970 s. Due to greater restrictions on PFOS globally in recent years, the production and use of F-53B correspondingly increased, consequently causing more emissions into the environment. In China, an increasing number of studies report frequent detection and broad exposure to F-53B in the natural environment, various wildlife and the human body. In human blood, the detection rate of F-53B is almost 80%, accounting for 8.69 to 28% of ∑per- and polyfluoroalkyl substances (PFASs). F-53B is the most biopersistent PFAS in humans to date, with a half-life of 15.3 years. In addition, F-53B displays protein binding affinity and high human placental permeability. Recently, some epidemiological studies have reported the health risks associated with F-53B in humans, including abnormal serum lipid metabolism, vascular dysfunction, endocrine disorders and even adverse birth outcomes. Various in vivo and in vitro studies have demonstrated the toxicity of F-53B, such as hepatotoxicity, interference effects on the endocrine system, as well as reproductive and developmental toxicity. Our aims are to review studies on human F-53B exposure levels, trends and associated health effects; evaluate the potential toxicity; and predict directions for future research.